Penyuluhan tentang Keselamatan dan Kesehatan Kerja (K3) Bagi Pengrajin Kapal Kayu di Galangan Kapal Rakyat Kabupaten Takalar - Mohammad Rizal Firmansyah; Syamsul Asri; Farianto Fachruddin; Wahyuddin Wahyuddin; Wihdat Djafar; Fadhil Rizki Clausthaldi; Ganding Sitepu; Rosmani Rosmani; Andi Siti Chaerunnisa; Muh. Akbar Aziz (Faculty of Engineering UNHAS, 2022)
The process of wooden boats building in a traditional wooden boat shipyards in South Sulawesi is still carried out in the traditional way. Their ship building expertise and techniques were passed down from generation to generation from their predecessors. Hence, the current method of building ships is still the same as their predecessors. However, the current craftsmen are using electrical equipment already to help to complete their work, such as electrical cutting machine for cutting wood, boards or pegs. As with their predecessors, in building their ships, they have not implemented occupational safety and healthy (OSH) in their ship building procedures. In an initial interviews with wooden ship craftsmen, it was found that several wooden ship craftsmen had experienced work accidents which resulted in minor and serious injuries and in one or two cases some died. Therefore, it is necessary to introduce occupational safety and healthy (OSH) for wooden ship craftsmen at the traditional shipyards in South Sulawesi. The partners for this activity were the wooden ship craftsmen group called “Torani” in Galesong District, Takalar Regency. The aim is to provide an understanding of the importance of OSH aspects and then apply preventive measures to activities that can cause accidents and occupational health problems in their work environment. The result shows that all craftsmen have understand the importance of OSH aspects in their daily work.